Distribution of Pyrimidine Oligonucleotides in Strands L and H of Bacillus subtilis DNA - Rudner, Rivka (1972)
The distribution of pyrimidine oligodeoxynucleotide clusters in L and H strands of Bacillus subtilis DNA separated by methylated albumin-Kieselguhr has been determined. Preparations of native and single-stranded DNA were degraded with diphenylamine in formic acid, and the released isostichs with the general formula of Py(n)P(n+1) were separated on DEAE-cellulose by chain length. Eleven isostichs were obtained for strands L and H in unequal proportions. Each isostich fraction was subfractionated by base composition on DEAE-cellulose at pH 3.0. 61 Pyrimidine oligonucleotide clusters were separated from the H strand and only 46 from the L strand. The findings show a higher degree of asymmetry between the strands in the distribution of cytosine-rich clusters as compared with thymine-rich clusters. The longest cytosine oligodeoxynucleotide present in both strands is of chain length 5. There is an unusually high distribution of thymine oligodeoxynucleotides of length 5-11. Up to chain length 6, the distribution of thymine oligodeoxynucleotides between the strands is about equal; from chain length 7 to 11 they occur predominantly in the H strand.